The effect of organizational learning dimensions on availability of learning organization dimensions in Iraqi planning ministry - طاهر فاضل جميل (Journal of Economics and Administrative Sciences, 2011)
The aim of this research to study. The dimensions of organizational learning have been defined(learning dynamics, individuals empowerment, knowledge management and technology application) as well as the dimensions of learning organization have been defined (culture values, knowledge transfer, communication and employee characteristics), Asset completion questionnaire was used to collect data of this research from a purposely sample represent forty employees who works in Iraqi Planning Ministry at different positions. The research divided to four parts : The first to the research methodology, the second to the theoretical review of the research, the third to analysis and discuss the empiric results and the last to the conclusions and recommendations. The most outstanding results reached by researcher was effect of organizational learning dimensions on availability of learning organization dimensions in the ministry researched.